Calcium and phosphate metabolism in acute falciparum malaria. - Davis, T; Pukrittayakamee, S; Woodhead, J; Holloway, P; Chaivisuth, B; White, N (1991)
1. Mineral homeostasis was investigated in 172 Thai adults with acute falciparum malaria at presentation (87 males, 85 females; mean age 30 years), and prospectively in a subgroup of 10 severely ill patients. 2. Mild, asymptomatic hypocalcaemia (corrected plasma calcium concentration 1.79-2.11 mmol/l) was found in 61 cross-sectional study patients (35.5%), with no difference between those with uncomplicated (2.16 +/- 0.10 mmol/l, mean +/- SD, n = 89) and severe (2.18 +/- 0.15 mmol/l, n = 83, P = 0.36) infections. Six prospectively studied patients were hypocalcaemic during treatment; simultaneous serum intact parathormone concentrations were inappropriately low (less than 5.0 pmol/l), but rose in three patients to high levels (11.8-16.4 pmol/l) on the fifth day. 3. Plasma phosphate concentration was decreased (less than 0.80 mmol/l) on admission in 74 patients (43.0%) and increased (greater than 1.45 mmol/l) in 15 (8.7%). Severe phosphate depletion (plasma phosphate concentration less than 0.30 mmol/l) occurred in 14 patients, of whom 11 had severe infections. Serum phosphate concentrations in the prospective study patients on admission (0.59 +/- 0.23 mmol/l) correlated significantly with the simultaneous renal threshold phosphate concentration (0.68 +/- 0.33 mmol/l; r = 0.607, P less than 0.025) and both parameters rose in parallel during treatment. 4. Plasma magnesium concentrations were normal (0.75-1.05 mmol/l) in 108 patients (62.8%); 45 cases (26.1%) had hypermagnesaemia and 19 (11.0%) had hypomagnesaemia. 5. These data suggest that mild hypocalcaemia is common in malaria regardless of disease severity; a depressed parathormone response may contribute. Despite malaria-associated haemolysis, hypophosphataemia is also common, but can be severe.(ABSTRACT TRUNCATED AT 250 WORDS)